2005
DOI: 10.1038/sj.onc.1208476
|View full text |Cite
|
Sign up to set email alerts
|

Visinin-like protein-1 is a potent inhibitor of cell adhesion and migration in squamous carcinoma cells

Abstract: Tumor cell invasion is a highly integrated and complex process comprising several biologically distinct functions such as cell adhesion, motility, proteolysis, etc. Visininlike protein-1 (VILIP-1), a member of the neuronal EFhand calcium-sensor protein family, plays a role in regulating tumor cell invasiveness of mouse squamous cell carcinoma (SCC). VILIP-1 enhances cyclic adenosine monophosphate levels through PKA induction. However, the mechanism by which VILIP-1 reduces cell invasiveness is not well underst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
41
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 36 publications
(47 citation statements)
references
References 36 publications
(30 reference statements)
5
41
0
Order By: Relevance
“…The present data also indicated that some genes (such as VSNL1 in NB cell lines, and PQLC3 in both SCLC and NB cell lines) are consistently down-regulated regardless of their amplification status. VSNL1 down-regulation has been already reported in squamous carcinoma cells (Gonzalez Guerrico et al 2005) and in non-small cell lung carcinomas (Fu et al 2008). Our data suggest that it may have a tumor suppressor role also in NB tumors.…”
Section: Double Minutes and Hsr In Solid Tumorssupporting
confidence: 55%
“…The present data also indicated that some genes (such as VSNL1 in NB cell lines, and PQLC3 in both SCLC and NB cell lines) are consistently down-regulated regardless of their amplification status. VSNL1 down-regulation has been already reported in squamous carcinoma cells (Gonzalez Guerrico et al 2005) and in non-small cell lung carcinomas (Fu et al 2008). Our data suggest that it may have a tumor suppressor role also in NB tumors.…”
Section: Double Minutes and Hsr In Solid Tumorssupporting
confidence: 55%
“…Basal epidermal keratinocytes of normal murine skin express VILIP-1, whereas its expression is markedly decreased in aggressive and invasive squamous cell carcinomas (8). Enforced expression of VILIP-1 led to inhibition of cell adhesion and migration by down-regulating fibronectin receptors, suggesting a tumor suppressor function for VILIP-1 (9). Similarly, VILIP-1 expression is present in normal squamous epithelium of esophagus and bronchial mucociliary epithelium.…”
Section: Vilip-1mentioning
confidence: 86%
“…Previous results suggest VSNL1 regulates heart natriuretic peptide receptor B [93]. The VSNL1 gene also plays a critical role in regulating cell adhesion and migration via downregulation of fibronectin receptor expression [95]. The VSNL1 gene is highly expressed in the nervous system.…”
Section: Discussionmentioning
confidence: 99%